Dispersão de grafeno e óxido de grafeno em matrizes poliméricas - Araujo, Mayara Cardoso de (2020)
Polymer nanocomposites obtained by the insertion of two-dimensional (2D) filler via melt mixing have been the subject of study by several researchers due to the increase in the mechanical, thermal and electrical properties that these particles can provide to the polymer. This increase in the mentioned properties depends directly on the dispersion of the nanoparticles in the matrix and the interaction generated between filler and polymer. This work deals with to the preparation and characterization of nanocomposites based on linear low density polyethylene - LLDPE and Poly (butylene adipate-co-terephthalate) - PBAT as matrices and graphene (G) and graphene oxide (GO) as fillers, and thus evaluate the interaction of these charges with each type of polymer and how this is reflected in the physical properties of these materials. Graphite oxide (GrO) obtained by the Hummers method was characterized by Raman spectroscopy, X-ray diffraction (XRD) and thermogravimetric analysis (TGA). Then, ultrasound exfoliation was performed to obtain graphene oxide (GO), with later characterization by atomic force microscopy (AFM). The commercial graphene acquired was analyzed and Raman spectroscopy signaled a graphene containing few layers. The nanocomposites were obtained by melt mixing using the Solid Solid Deposition method in a twin-screw extruder, using filler concentrations between 0 - 0.3% in weight. The nanocomposites were characterized by different techniques: mechanical analysis (tension), rheological analysis, dynamic-mechanical analysis (DMA), differential scanning calorimetry (DSC), X-ray diffraction (XRD) and scanning electron microscopy (SEM). The LLDPE/G nanocomposites showed significant increases in mechanical properties for all compositions used, higher than the results obtained for LLDPE/GO. Likewise, graphene nanocomposites showed less damping factor (tan ) compared to graphene oxide nanocomposites. Both nanoparticles acted as nucleating agents for LLDPE and showed no evidence of re-stacking in the polymeric matrix. However, only the LLDPE/G nanocomposite (0.05%) showed the formation of a plateau in the storage modulus (G ') at low frequencies in rheological analysis. The PBAT / GO nanocomposites showed higher Young's modulus, deformation at break and toughness in mechanical tests compared to PBAT/G. Graphene oxide aided the PBAT crystallization process and increased its crystallinity at concentrations of 0.05% and 0.3%. Graphene also acted as a nucleating agent for PBAT, even with the indication of its re-stacking in the polymer. In rheological tests, only PBAT/GO nanocomposites exhibited the beginning of the formation of a plateau in the storage modulus (G ') at low frequencies. These results indicate that the LLDPE/G and PBAT/GO systems have the best distribution and dispersion of nanoparticles in the polymeric matrix, due to their greater interaction between load and polymer, which promotes a greater increase in the properties of nanocomposites.